2018
DOI: 10.2147/idr.s172144
|View full text |Cite
|
Sign up to set email alerts
|

Application of <em>tuf</em> gene sequence analysis for the identification of species of coagulase-negative staphylococci in clinical samples and evaluation of their antimicrobial resistance pattern

Abstract: IntroductionCoagulase-negative staphylococci (CoNS) are normal inhabitants of human skin and mucous membranes. However, CoNS represent one of the major nosocomial pathogens, especially in immunocompromised patients. The increasing incidence of CoNS and mainly methicillin-resistant strains underlines the need for an accurate identification of Staphylococcus isolates at the species level. Analysis of the tuf gene proved to be an accurate tool for the species identification of CoNS. The aims of this study were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Several studies have identified S. epidermidis as the most commonly isolated CoNS. 22 , 25 – 29 In contrast, some studies have suggested S. capitis 30 and S. hemolyticus 10 , 31 , 32 as the most common CoNS. S. epidermidis is the most common commensal of our skin and mucosa, and contamination through the devices during medical procedures are very common.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified S. epidermidis as the most commonly isolated CoNS. 22 , 25 – 29 In contrast, some studies have suggested S. capitis 30 and S. hemolyticus 10 , 31 , 32 as the most common CoNS. S. epidermidis is the most common commensal of our skin and mucosa, and contamination through the devices during medical procedures are very common.…”
Section: Discussionmentioning
confidence: 99%
“…All staphylococcal strains were identified by using both a Vitek 2 system (BioMérieux, France) and 16S rRNA sequencing (Cosmogenetech, Korea). Sequencing of tuf gene was also performed to confirm S. schleiferi isolates [12]. Coagulase production was confirmed as described in previous research [13].…”
Section: Methodsmentioning
confidence: 99%
“…The coagulase-negative Staphylococcus was resistant to oxacillin in almost half of our patients. A study by Khosravi et al 24 supported this result. These authors also described that this bacterium was not susceptible to trimethoprim + sulfamethoxazole, which is in contrast with our data.…”
Section: Discussionmentioning
confidence: 79%